The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1016/j.visres.2019.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Monocular accommodation response to random defocus changes induced by a tuneable lens

Abstract: Accommodation of the human eye relies on multiple factors and visual cues that include object size, monochromatic and chromatic aberrations, and vergence. Yet, even in monocular conditions, accommodation corrects for defocus. Studies of eye growth in chicks have addressed whether the retina can decode the sign of defocus as this may play a role for emmetropization and possibly also accommodation. However, findings have not been unambiguous and questions remain. Here, we report on monocular accommodation studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…The Strehl ratio was obtained at a level greater than 0.9. Sharmin and Vohnsen (2019) showed that the diameter of the focal spot size with defocus when normalized to a 2.5-μm center-to-center cone spacing decreases for different pupil diameters. Changes in the radii of corneal curvatures and the relative positions of the cornea, lens, and retina are required for maintenance of ocular image quality when the eye is subjected to small variations in IOP.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Strehl ratio was obtained at a level greater than 0.9. Sharmin and Vohnsen (2019) showed that the diameter of the focal spot size with defocus when normalized to a 2.5-μm center-to-center cone spacing decreases for different pupil diameters. Changes in the radii of corneal curvatures and the relative positions of the cornea, lens, and retina are required for maintenance of ocular image quality when the eye is subjected to small variations in IOP.…”
Section: Methodsmentioning
confidence: 99%
“…This is only possible with negative defocusing if the light is focused behind the retina. However, Sharmin and Vohnsen (2019) showed that small fluctuations in the stimulus to accommodation (in the range of 0.25 D) do not induce an accommodative response, which is especially noticeable for larger pupil sizes. Sharmin and Vohnsen (2019) investigated the reaction of the lens to a variable stimulus up to 2.5 D, appearing at a frequency of 0.1 Hz.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations